Development and characterisation of fast dispersible dimenhydrinate tablets: Compactional study and in-silico PBPK modeling - Uroosa Maqbool; Farya Zafar; Riffat Yasmin; Huma Ali; Hira Akhtar; Rizwana Rehmat; Yumna Tahir; Iqra Haider; Shumaila Anwar; Javeria Ameer (PLoS ONE, 2025)
The aim of this study was to optimize and evaluate dimenhydrinate fast dispersible tablets (50 mg) by utilizing cost effective direct compression method. A total of nine formulations (F1-F9) were designed and developed by central composite rotatable design using design expert ® software (version 11.0, Stat-Ease Inc.,) to study the impact of avicel PH102 (15–55%) and sodium starch glycolate (2–8%) on responses, i.e., hardness (R 1 ), disintegration time (R 2 ) and % drug release (R 3 ). Powder blends of all formulations showed good flow behavior. Post compressional studies were conducted to assess the quality attributes of the compressed formulations. Formulation F2 was found to be optimized with good mechanical strength, i.e., hardness 4.2 kg, friability 0.77%, disintegration time 19 secs and % drug release 100.01% at 15 minutes. Compressional behavior of optimized formulation was determined with the help of Heckle plot. The PY (yield value) and the tensile strength of the optimized formulation (F2) were found to be 66.66 MN/m 2 and 1.093 ± 1.66 to 1.642 ± 1.76 MN/m 2 respectively. Differential scanning calorimetric and scanning electron microscopy analysis were performed to explore compatibility between ingredients and morphological features. All formulations followed weibull model in four different dissolution media. All the formulations were found to be stable at accelerated conditions. The in-silico GastroPlus™ PBPK modeling was also carried out to determine the pharmacokinetic parameters of the optimized formulation (F2) as an alternative to in vivo dimenhydrinate studies. Simulated PK values of F2 were found to be 143.16 ng/ml (C max ), 2 h (T max ), 2533.8 ng-h/ml (AUC 0-inf ) and 1477.9 ng-h/ml (AUC 0-t ). Results indicated that the fold error value was > 2 which indicated that experimental values are comparable with the predicted values. This type of study will be helpful for pharmaceutical manufacturers to produce patient compliance, low-cost tablet dosage form.